Toward An Open Integralism: Multi-Religious Interactions In Sumberjo, Kediri - Saputra, Riza; Handayani, Andri; Mujab, Saiful (Universitas Islam Negeri Raden Intan Lampung, 2020)
This research reveals some perspectives of multi-religious interaction in Sumberjo hamlet concerning the forms of tolerance and the role of the environment. Sumberjo Hamlet exemplifies social awareness in a variety of religious life and has successfully presented social solidarity among distinct traditions of each religious group. There are four major religions living in Sumberjo Hamlet, namely, Islam, Hindu, and Christianity (both Protestantism and Catholics). This research aims at finding the processes of multi-religious interaction in Sumberjo Hamlet, the form of religious tolerance, and the role of the religious environment in building multi-religious tolerance. Conducting a semi-structured interview to the villagers, religious leaders, and village official, the study reaches the following results, firstly, there are three forms of religious tolerance in Sumberjo hamlet, and these three categories are Understanding, Openness, and Respect. Secondly, there are three periods of multi-religious interaction in Sumberjo hamlet, these three periods are: exclusivism, Inclusivism, and Open Integralism,. Thirdly, there are some roles of environment which give contribution in social and individual life: Social consciousness, Social solidarity, and Social humanism